A Case Report of Neonatal Beckwith-Wiedemann Syndrome and Literature Review - ZENG Liuyu, YANG Xiufang (Zhongguo quanke yixue, 2024)
Beckwith-Wiedemann syndrome (BWS) is a growth disorder in which BWS is associated with aberrant expression of genes imprinted in the critical region of BWS and is considered a clinical spectrum in which affected individuals may have many or only one or two typical clinical features. Postnatal neonatal screening is particularly important to facilitate early diagnosis and treatment of this disorder. In this paper, we report a case of a neonate with a large tongue as the first symptom, hypoglycemia during hospitalization, and umbilical hernia in the late follow-up, and genetic testing results suggesting that he carried a c.235T>C (p.Trp79Arg) variant as a missense variant in the coding region of the cyclin dependent kinase inhibitor 1C (CDKN1C) gene, and that a T→C transition in nucleotides at position 235 of the CDKN1C gene, i.e., a missense mutation in the amino acid located in amino acid 79. This resulted in the mutation of tryptophan to arginine. Combining the clinical features of the child with the genetic test results, the diagnosis of BWS was confirmed. The purpose of this case report and the related genetic research progress is to improve the understanding of the clinical diagnosis and treatment of BWS, and to avoid misdiagnosis and under-diagnosis.